Political Education for New Voters Insight into Democracy as an Intelligent Citizen - Kalfin; Sulistya A, Astrid (Communication in Research and Publications (CRP), 2024)
New voters consisting of students, college students or voters with an age range of 17 to 21 years are a unique segment, often giving rise to surprises and certainly promising in terms of quantity. This study aims to describe the importance of political education for new voters in general elections in order to become smart voters and understand the political dynamics that occur. The study method used is a library research approach. Data and information collection techniques are carried out by utilizing documents in the form of articles, manuscripts, books, and other relevant documents for analysis. Data and information analysis is carried out using a descriptive analysis method. The results of the study show that it is important for new voters to be given education so that they have the right political literacy. Education for new voters as a source of learning for civic education to increase the political participation of new voters participating in education. Active participation of new voters as citizens in political activities is part of the measure of the effectiveness of the democratization process. The contribution of the results of this study is expected so that every citizen, especially new voters, is able to play a role as an intelligent, democratic, and characterful and civilized citizen.